Local Government Investment in Financial Performance: Evidence from Local Government in Indonesia - Suci Deliya Natasya; Mustamin Mustamin; Andi Chairil Furqan; Tenripada Tenripada (Yayasan Riset dan Pengembangan Intelektual, 2025)
Indonesia's national development goals focus not only on improving social welfare but also on creating an inclusive and sustainable investment climate. This study aims to analyze the influence of regional financial performance on regional investment levels in Indonesia, with a focus on financial independence and flexibility. This study uses quantitative methods. The data used covers 420 provinces/regencies/cities in 2021 and 2022 with a total of 840 observations, which were analyzed using multiple linear regression. The results show that regional financial independence has a positive and significant effect on investment levels, reflecting the region's ability to manage resources independently. Regional financial flexibility also has a positive and significant effect, with the ability to adjust budgets that support sustainable development and investment. The results of this study indicate that the combination of financial independence and flexibility creates a sustainable investment climate, especially in the fields of foreign direct investment (FDI) and domestic direct investment (DDI). The implications of this study demonstrate the importance of adaptive and transparent regional financial management to increase investment attractiveness and accelerate regional economic growth in Indonesia. This study has limitations in the scope of variables that only cover two financial performance indicators out of six available indicators, as well as limited data until 2022. Future studies are recommended to add other relevant variables such as human resource quality, risk management index, political stability and infrastructure, as well as conduct longitudinal analysis with annual data and a cross-regional approach among developing countries.